2021
DOI: 10.1111/jcpe.13472
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory potential is associated with poor periodontal health: A population‐based study

Abstract: Aim To investigate the association between dietary inflammatory potential and poor periodontal health. Material and Methods A cross‐sectional analysis of a nationally representative sample of participants was performed. NHANES 2011–2014 (n = 7081) and NHANES 2001–2004 (n = 5098) were used as discovery and validation datasets, respectively. The energy‐adjusted dietary inflammatory index (E‐DII) score was calculated for each participant based on 24‐h dietary recalls to assess diet‐associated inflammation. Period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 47 publications
2
66
0
Order By: Relevance
“…The method involves the grouping of nutrients, foods, or food groups that are commonly consumed together. A number of studies have used dietary pattern analysis to examine the relationship between diet and periodontal disease (Al-Zahrani et al, 2005;Bawadi et al, 2011;Jauhiainen et al, 2016Jauhiainen et al, , 2020Salazar et al, 2018;Wright et al, 2020;Alhassani et al, 2021;Li et al, 2021). Most of these studies have used a "priori" approach, which evaluates dietary intake using pre-defined scoring classifications based on dietary guidelines or knowledge of diet and disease relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method involves the grouping of nutrients, foods, or food groups that are commonly consumed together. A number of studies have used dietary pattern analysis to examine the relationship between diet and periodontal disease (Al-Zahrani et al, 2005;Bawadi et al, 2011;Jauhiainen et al, 2016Jauhiainen et al, , 2020Salazar et al, 2018;Wright et al, 2020;Alhassani et al, 2021;Li et al, 2021). Most of these studies have used a "priori" approach, which evaluates dietary intake using pre-defined scoring classifications based on dietary guidelines or knowledge of diet and disease relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have used a "priori" approach, which evaluates dietary intake using pre-defined scoring classifications based on dietary guidelines or knowledge of diet and disease relationships. For instance, consumption of a healthy diet measured by the Baltic Sea Diet Score (Jauhiainen et al, 2016(Jauhiainen et al, , 2020, the Recommended Finnish Diet Score (Jauhiainen et al, 2016(Jauhiainen et al, , 2020, the Healthy Eating Index (Al-Zahrani et al, 2005;Bawadi et al, 2011), and the Alternative Healthy Eating Index (Salazar et al, 2018) have all been associated with a reduced risk of periodontal disease, whereas consuming a pro-inflammatory diet measured by the energy-adjusted Dietary Inflammatory Index has been associated with periodontitis in US adults (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 27 or 28 food components in 24 HR were used to calculate the DII scores: energy, carbohydrate; protein; total fat; dietary fiber; cholesterol; saturated, monounsaturated, and polyunsaturated fatty acids; ω-3 and ω-6 polyunsaturated fatty acids; vitamins A, B1, B2, B3 (niacin), B6, B12, C, D, and E; folic acid; alcohol; beta-carotene; caffeine; iron; magnesium; zinc; and selenium. Previous studies confirmed that DII scores based on only 27 or 28 food parameters did not influence the predictive ability ( 13 , 21 ). Since we calculate DII scores according to participants' dietary recall information, we performed a consistency test to evaluate the accuracy of the measurement.…”
Section: Methodsmentioning
confidence: 59%
“…Although limited study about diet management in CKD focused on DII, previous studies could prompt us to connect diet intervention with DII in CKD. Typically, dietary patterns rich in red meat, saturated fats, and simple carbohydrates, higher and positive DII scores (pro-inflammatory diets) ( 10 ), while diets composed of vegetables, fruits, whole grains, legumes, nuts, and fish show more negative DII scores (anti-inflammatory diets) ( 36 ). The KIDIGO guideline recommended patients with glomerular disease to develop a plant-based diet and restrict sodium, fats and red meat intake ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The details of DII calculation are provided in the Supplementary Material . To minimize the influence of total energy intake, we designed an E-DII (E-DII, DII/total energy intake) as the exposure variable in this study ( 10 ).…”
Section: Methodsmentioning
confidence: 99%